SARS-CoV-2 proteases PLpro and 3CLpro cleave IRF3 and critical modulators of inflammatory pathways (NLRP12 and TAB1): implications for disease presentation across species. Issue 1 (1st January 2021) - Moustaqil, Mehdi; Ollivier, Emma; Chiu, Hsin-Ping; Van Tol, Sarah; Rudolffi-Soto, Paulina; Stevens, Christian; Bhumkar, Akshay; Hunter, Dominic J. B.; Freiberg, Alexander N.; Jacques, David; Lee, Benhur; Sierecki, Emma; et al.
ABSTRACT: The genome of SARS-CoV-2 encodes two viral proteases (NSP3/papain-like protease and NSP5/3C-like protease) that are responsible for cleaving viral polyproteins during replication. Here, we discovered new functions of the NSP3 and NSP5 proteases of SARS-CoV-2, demonstrating that they could directly cleave proteins involved in the host innate immune response. We identified 3 proteins that were specifically and selectively cleaved by NSP3 or NSP5: IRF-3, and NLRP12 and TAB1, respectively. Direct cleavage of IRF3 by NSP3 could explain the blunted Type-I IFN response seen during SARS-CoV-2 infections while NSP5 mediated cleavage of NLRP12 and TAB1 point to a molecular mechanism for enhanced production of cytokines and inflammatory response observed in COVID-19 patients. We demonstrate that in the mouse NLRP12 protein, one of the recognition site is not cleaved in our in-vitro assay. We pushed this comparative alignment of IRF-3 and NLRP12 homologs and show that the lack or presence of cognate cleavage motifs in IRF-3 and NLRP12 could contribute to the presentation of disease in cats and tigers, for example. Our findings provide an explanatory framework for indepth studies into the pathophysiology of COVID-19.